The first reported case of California encephalitis in more than 50 years. - Eldridge, B F (Centers for Disease Control and Prevention, 2001)
A recent case of California encephalitis, a rare mosquito-borne viral disease, represents only the fourth ever reported and the first since the initial three cases in 1945. This case was diagnosed retrospectively on the basis of a rise in antibody titer between acute- and convalescent-phase serum samples.